Application of SARS-CoV-2 Antigenic Test in asymptomatic workers: sensitivity and specificity of the test - Visci, Giovanni; Zunarelli, Carlotta; Violante, Francesco; Boffetta, Paolo (La Medicina del Lavoro, 2021)
Background. Healthcare workers (HCW) are at increased risk of being infected with SARS-CoV-2; while PCR test remains gold standard for diagnosis of COVID19 infection, antigen based rapid detection tests have been recently approved by OMS. Methods. We pooled data on occupational surveillance of 6397 asymptomatic HCW and other employees who were tested for SARS-CoV-2 infection at the University Hospital in Bologna using rapid antigen test between November 16, 2020 and January 29, 2021. Findings. A total of 17,993 rapid tests were performed, of which 704 for contact with an infected person and 17,289 for voluntary screening. Among 17,732 tests with valid results, 87 tested positive (0.49%) and 17 weakly positive (0.10%). The sensitivity of the antigenic test was 88.6% (81.1-96.1), the specificity was 93.4% (89-97.8), the positive predictive value, given a prevalence of infection of 42.1%, was 90.7% (84.8-96.6).